Family Separation and Lives in Limbo: U.S. Immigration Policy in the 1920s and during the Trump Administration. Issue 1 (July 2020) - Schacher, Yael
Drawing on the author's work with refugees and asylum seekers in the United States, this article examines policies and practices related to family separation among immigrants in the 1920s and now. I use data collected from historical archives and firsthand interviews with refugees and asylum seekers and describe how restrictions on the admission of relatives leaves immigrants and refugees in the United States feeling unsettled and divided. I compare the situation in the 1920s to more recent years, when the federal government has pursued policies to restrict admission and impede integration.